2006
DOI: 10.1007/s11060-006-9159-4
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Docetaxel (Taxotere), Carmustine and Combined Interstitial Therapy: a Novel Treatment for Experimental Malignant Glioma

Abstract: Docetaxel (Taxotere ® ) is a hemisynthetic, anti-cancer compound with good preclinical and clinical activity in a variety of systemic neoplasms. We tested its activity against malignant gliomas using local delivery methods. Antitumor activity was assessed in vitro against human and rat brain-tumor cell lines. For in vivo evaluation, we incorporated docetaxel into a biodegradable polymer matrix, determined associated toxicity in the rat brain, and measured efficacy at extending survival in a rat model of malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Herein, each factor requires different time scales and concentration profiles because of the nature of the repair/inhibition process. This suggests that the sequential or coupled release of multiple factors with different temporal profiles will become essential and critical for a successful tissue regeneration or tumor inhibition strategy 1–12. However, in modern design, most delivery systems only accounts for a single factor, limiting the overall efficacy of the therapy 13–19.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, each factor requires different time scales and concentration profiles because of the nature of the repair/inhibition process. This suggests that the sequential or coupled release of multiple factors with different temporal profiles will become essential and critical for a successful tissue regeneration or tumor inhibition strategy 1–12. However, in modern design, most delivery systems only accounts for a single factor, limiting the overall efficacy of the therapy 13–19.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when inulin, a large molecule that has less potential to cross the blood–brain barrier, is administered by wafer technology, the inulin persists in the brain for a longer period of time and diffuses a larger distance from the brain/polymer interface. The feasibility of polifeprosan 20 polymer as a slow release delivery technology for alternative therapeutic agents has been demonstrated in preclinical models using paclitaxel,60 IUDR,61,62 temozolomide,63 taxotere64 camptothecin,65,66 tiripazamine,67 and other agents. When more effective agents are identified, this may be considered again.…”
Section: Wafer Technology: Possible Renewed Interest In the Future?mentioning
confidence: 99%
“…In addition, various chemotherapeutic agents other than BCNU have been exploited to deliver through polymeric system. Preclinical studies demonstrated that many drugs such as temozolomide, paclitaxel, taxotere, and camptothecin were efficacious against gliomas through polymeric delivery (46)(47)(48)(49). Further clinical investigation of the safety and efficacy is therefore warranted.…”
Section: Economic Considerationmentioning
confidence: 99%